Pelatihan Strategi Pengenalan Bahasa Inggris pada Siswa PAUD bagi Guru PAUD Wineha di Diwek Jombang - Laili, Elisa Nurul; Zuhriyah, Mukminatus; Fajarina, Maskhurin; Ma’rifatulloh, Sayid; Agustina, Ria Kamilah (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Children, especially at the early childhood education level, are the nation's assets who will become future state leaders. Therefore, introducing English to elementary school children is crucial to enhance their abilities to pursue higher education. Learning and familiarizing themselves with English, as an international language of communication, can begin with reading, pronouncing, and forming simple sentences. An analysis of the situation at PAUD Wineha in Keras Village, Diwek Subdistrict, Jombang Regency, shows that PAUD teachers need "Training in English Introduction Strategies" to address students in the modern era. The results indicate that participants agree that teaching English in early childhood education is essential for several reasons, including skill-building, keeping up with the times, and providing a foundation for future educational journeys. According to the questionnaire results, the training was very good. Participants expressed their happiness and anticipation for future training sessions. They also noted that they appreciated the quality of the training and experienced positive feelings such as enthusiasm and excitement during the event.